THE ROLE OF SOCIAL CAPITAL IN MEDIATING FINANCIAL LITERACY AND FINANCIAL TECHNOLOGY (FINTECH) TOWARDS FINANCIAL INCLUSION IN FASHION SMEs IN GEDANGAN DISTRICT SIDOARJO REGENCY - Ni'mah, Nailatun; Anwar, Muhadjir (Yayasan Education and Social Center, 2024)
This study aims to analyze the impact of financial literacy and financial technology (FinTech) on financial inclusion with social capital as a mediator for fashion SMEs in Gedangan District, Sidoarjo Regency. In the digital age, technology has become a primary need facilitating various activities, including financial sector advancements through FinTech. Financial literacy and FinTech adoption are crucial factors in enhancing financial inclusion, particularly for SMEs. This research also examines the role of social capital as a mediator that can strengthen the relationship between financial literacy and FinTech with financial inclusion. Using the Theory of Planned Behavior (TPB) approach, this study identifies that attitudes towards behavior, subjective norms, and perceived behavioral control are influencing factors in individuals' intentions to access financial services. The findings indicate that financial literacy and FinTech have a significant impact on financial inclusion, with social capital playing a significant mediating role in this relationship.